THE EFFECTIVENESS OF 3-2-1 STRATEGY IN TEACHING READING COMPREHENSION ON NARRATIVE TEXT - Sesilia, Susi; Susilawati, Endang; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The aim of this research was to find out the effectiveness of 3-2-1 strategy in teaching reading comprehension on narrative text to the tenth grade students of SMA Santo Fransiskus Asisi Pontianak in academic year 2014/2015. The research method was a pre-experimental research with one group of pre test and post test design and the sample was clas X B which consists of 30 students. The research found that 3-2-1 strategy was effective in teaching reading comprehension on narrative text to the tenth grade students of SMASanto Fransiskus Asisi Pontianak. It is based on the data calculation that the degree of the effectiveness was 1, 01 and it was categorized as high. In conclusion, the effectiveness of 3-2-1 strategy in teaching reading comprehension on narrative text to the tenth grade students of SMA Santo fransiskus Asisi pontianak in academic year 2014/2015 can be categorized as high. Keywords: Reading Comprehension, Narrative Text, 3-2-1 Strategy Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifan dari strategi 3-2-1 dalam mengajarkan pemahaman membaca teks narratif pada siswa kelas X SMA Santo Fransiskus Asisi Pontianak pada tahun pelajaran 2014/2015. Metode penelitian yang digunakan adalah metode pre-experimental dengan model satu grup dari pre-test dan post-test dan sampel dari kelas X B yang berjumlah 30 siswa. Hasil penelitian menunjukkan bahwa 3-2-1 strategi efektif dalam mengajar pemahaman membaca teks narratif pada siswa kelas X SMA Santo Fransiskus Asisi Pontianak. Hal tersebut di buktikan dengan perhitungan data bahwa tingkat dari keefektifan adalah 1,01 yang tergolong kategori tinggi. Jadi, keefektifan dari 3-2-1 strategy dalam mengajarkan pemahaman reading pada teks narratif pada siswa kelas 10 SMA Santo Fransiskus Asisi Pontianak pada tahun akademik 2014/2015 di kategorikan sebagai tinggi. Kata kunci: Pemahaman Reading, Teks Narratif, 3-2-1 Strategy